Freehand S2 Alar-Iliac Screw Placement Using K-Wire and Cannulated Screw : Technical Case Series - Choi, Ho Yong (J Korean Neurosurg Soc, 2018)
OBJECTIVE: Among the various sacropelvic fixation methods, S2 alar-iliac (S2AI) screw fixation has several advantages compared to conventional iliac wing screw. However, the placement of S2AI screw still remains a challenge. The purpose of this study was to describe a novel technique of free hand S2AI screw insertion using a K-wire and cannulated screw, and to evaluate the accuracy of the technique. METHODS: S2AI screw was inserted by free hand technique in sixteen consecutive patients without any fluoroscopic guidance. The gearshift was advanced to make a pilot hole passing through the sacroiliac joint and directing the anterior inferior iliac spine. A K-wire was placed through the pilot hole. After introducing a cannulated tapper along with the K-wire, a cannulated S2AI screw was installed over the K-wire. RESULTS: Thirty-three S2AI screws were placed in sixteen consecutive patients. Thirty-two screws were cannulated screws, and one screw was a conventional non-cannulated screw. Thirty out of 32 (93.8%) cannulated screws were accurately positioned, whereas two cannulated screws and one non-cannulated screw violated lateral cortex of the ilium. CONCLUSION: The technique using K-wire and cannulated screw can provide accurate placement of free hand S2AI screw.